IFPRI and the abolition of the wheat flour ration shops in Pakistan: a case-study on policymaking and the use and impact of research - Islam, Yassir; Garrett, James L. (International Food Policy Research Institute, 1997)
In February 1987, the Government of Pakistan (GOP) abolished the wheat ration shop system. Started as a food rationing program during World War II in colonial India, it had degenerated by the 1980s into a wasteful corrupt system that failed to reach the poor. Why did it take so long for this monument to come tumbling down? Was this simply fortuitous, or was it a well-planned and timed demolition? Our findings suggest that IFPRI research on this issue, commissioned and conducted in Pakistan, played a key role in this historic decision. A case study of this decision represents one means by which IFPRI can gauge the impact of its work on policy choices. In order to understand IFPRI's contribution to the outcome, this paper looks closely at how the information was produced, communicated, and used in the policymaking process leading to the decision. This analysis can suggest whether, and how, IFPRI's work mattered in the final decision to eliminate the ration shops, and provide lessons about what IFPRI can do to increase both the relevance and impact of its research activities. Understanding how information is used in policymaking at the country-level should also provide valuable insights that can be applied when analyzing the impact of research at the regional or international level, a hallmark of IFPRI's research strategy. This case study is also important because it is one of the few attempts to identify a particular body of IFPRI research and trace its use by policymakers in the decisionmaking process.